Diagnostic Challenge of Lupus with Overlap Syndrome in an Adolescent: A Case Report - Anu Suria Ganason; Mohd Radzniwan A. Rashid; Fathima Begum Syed Mohideen; Syed Mohamad, Sharifah Najwa; Nurul Hayati Chamhuri (Malaysian Journal of Science Health & Technology, 2024)
Lupus with overlap syndrome is an uncommon autoimmune disease that typically affects teenage females. It can present as various symptoms affecting multiple organs. Delay in the diagnosis of lupus will lead to deleterious effects on the implicated adolescents’ health. The case report aims to describe the diagnostic challenge of a refractory skin disease leading to a delay in diagnosis and highlight its psychosocial impact. Here, we describe a case of a teenager who presented with poorly controlled chronic dermatitis. The chronic dermatitis was refractory to the first-line therapy of topical steroids and emollients. She was finally diagnosed with lupus and overlap syndrome, confirmed by a skin biopsy. In conclusion, any chronic refractory skin diseases warrant further referral and investigation at the tertiary centre. Assessment of psychosocial in managing chronic skin disease in adolescent is essential as it could implicate their mental health further.